Faktor-Faktor Yang Berhubungan Dengan Jenis Penyakit Degeneratif - Loing, Atalarik Jonathan; Mandias, Reagen Jimmy (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
Epidemiological transition in the causes of death from infectious diseases to non-communicable or degenerative diseases. This phenomenon is closely related to the adoption of prolonged unhealthy lifestyles, thereby increasing the risk of degenerative diseases in the community. The objective of this study was to analyse the relationship between physical activity, smoking behaviour, and alcohol consumption with the incidence of degenerative diseases in Rerer Village, Minahasa Regency, North Sulawesi, Indonesia. The present study adopted a quantitative design, employing a descriptive correlation approach through a cross-sectional method. The present study was conducted using a total sampling method, with 54 respondents participating. The data on patients with degenerative diseases was obtained from local health centre medical records, while data on physical activity, smoking behaviour, and alcohol consumption were collected using the International Physical Activity Questionnaire (IPAQ), the Glover Nilsson Smoking Behavioural Questionnaire (GN-SBQ), and the Alcohol Use Disorders Identification Test (AUDIT). The results demonstrated that, among the range of degenerative diseases examined, hypertension emerged as the most prevalent condition, affecting 30 individuals (55.6%). The majority of respondents (88.9%) were categorised as engaging in heavy physical activity, 85.2% were classified as light smokers, and 87.0% were identified as low risk for alcohol consumption. Chi-square analysis demonstrated that physical activity (p = 0.799), smoking behaviour (p = 0.367), and alcohol consumption (p = 0.002) were not associated with the outcome. The findings of this study suggest that, among the three risk factors examined, alcohol consumption emerged as the sole factor demonstrating a statistically significant correlation with the prevalence of degenerative diseases in Rerer Village. It is recommended that future studies explore the potential influence of other variables, such as diet, genetic factors, and obesity, on the incidence of degenerative diseases. Epidemiologis penyebab kematian di negara berkembang telah beralih dari communicable ke penyakit degenerative. Fenomena ini erat kaitannya dengan adopsi gaya hidup tidak sehat yang berkepanjangan, sehingga meningkatkan risiko penyakit degeneratif di masyarakat. Penelitian ini bertujuan untuk menganalisis hubungan antara aktivitas fisik, perilaku merokok, dan konsumsi alkohol dengan insidensi penyakit degeneratif di Desa Rerer Kabupaten Minahasa, Sulawesi Utara Indonesia. Desain kuantitatif digunakan dalam penelitian ini, dengan pendekatan korelasi deskriptif melalui metode cross-sectional. 54 responden dengan menggunakan total sampling, terlibat dalam penelitian ini. Data mengenai pasien dengan penyakit degeneratif diperoleh dari catatan medis pusat kesehatan setempat, sementara data mengenai aktivitas fisik, perilaku merokok, dan konsumsi alkohol dikumpulkan menggunakan International Physical Activity Questionnaire (IPAQ), Glover Nilsson Smoking Behavioural Questionnaire (GN-SBQ), dan Alcohol Use Disorders Identification Test (AUDIT). Hasil penelitian menunjukkan bahwa, dari semua penyakit degeneratif yang diteliti, hipertensi merupakan kondisi yang paling umum, mempengaruhi 30 individu (55,6%). Sebagian besar responden (88,9%) dikategorikan melakukan aktivitas fisik berat, 85,2% diklasifikasikan sebagai perokok ringan, dan 87,0% diidentifikasi berisiko rendah untuk konsumsi alkohol. Analisis chi-square menunjukkan bahwa aktivitas fisik (p = 0,799), perilaku merokok (p = 0,367), dan konsumsi alkohol (p = 0,002). Hasil penelitian ini menunjukkan bahwa dari tiga faktor risiko yang dianalisis, konsumsi alkohol adalah satu-satunya yang menunjukkan hubungan yang signifikan secara statistik dengan insidensi penyakit degeneratif di Desa Rerer. Disarankan penelitian berikutnya mengeksplorasi pengaruh potensial variabel lain seperti pola makan, faktor genetik, dan obesitas terhadap insidensi penyakit degeneratif.